2020
DOI: 10.1002/csr.2011
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and employee performance: The mediating role of employee engagement in the manufacturing sector of Pakistan

Abstract: Past research proposes that corporate social responsibility (CSR) affects employees' behaviors and attitude. However, the empirical evidence of this claim is limited particularly in the context of eastern developing economies like Pakistan. So, the study in hand is an effort to extend the existing CSR literature by investigating the impact of CSR on employee performance using the lens of social identity theory. Additionally, the study also investigates the intervening role of employee engagement (EE) in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 120 publications
(222 reference statements)
1
35
1
Order By: Relevance
“…CSR activities also significantly affect employees' loyalty. At the same time, the results confirmed that the employee's loyalty is higher, which has the positive impact on the company's performance and competitiveness (Stojanovic et al, 2020;Ali et al, 2020;Jia et al, 2019). Chen & Khuangga (2020) add that fair working conditions achieved through CSR implementations contribute to higher employee performance.…”
Section: Theoretical Backgroundmentioning
confidence: 60%
See 2 more Smart Citations
“…CSR activities also significantly affect employees' loyalty. At the same time, the results confirmed that the employee's loyalty is higher, which has the positive impact on the company's performance and competitiveness (Stojanovic et al, 2020;Ali et al, 2020;Jia et al, 2019). Chen & Khuangga (2020) add that fair working conditions achieved through CSR implementations contribute to higher employee performance.…”
Section: Theoretical Backgroundmentioning
confidence: 60%
“…This allows expressing a certain association with the results of Galvas ( 2016 Involvement of employees in the decision-making process, e.g. by knowing employee's opinion on the object of decision-making, from the point of view of psychology, has a significant influence on loyalty and involvement towards the company (Galvas, 2016;Stojanovic et al, 2020;Ali et al, 2020;Jia et al 2019). In this context, the research showed that the participatory management style is the most applied by Slovak entrepreneurs -this could reflect the fact that Slovak companies have the most active employees in the overall involvement in the company's activities -innovation and healthy competition between colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies tried to focus on the effects of CSR on internal stimulus of CSR such as employees' behaviour, such as employees' commitment, employees' motivation, employees' satisfaction, employees' productivity and performance. It was mostly found by those studies that CSR as an independent variable that integrate interests of all stakeholders is affecting positively the employees' commitment ( Ali et al., 2010 ; De Silva and Lokuwaduge, 2019 ; Weerasekara and Ajward, 2020 ; Zafar and Ali, 2016 ), employees' motivation ( Jie and Hasan, 2016 ; Skudiene and Auruskeviciene, 2012 ), employees' satisfaction ( Barakat et al., 2016 ; Brancato, 2017 ; Wisse et al., 2018 ), employees' productivity ( Romi et al., 2018 ) and employees’ performance ( Ali et al., 2020 ; Story and Castanheira, 2019 ). Compared to this volume of studies on CSR, less study was performed on the leadership as an influential internal stimulus and their mutual effects on CSR.…”
Section: Discussionmentioning
confidence: 99%
“…Based on SIT, individuals consider themselves as salient to social categories, and individuals’ self-conception is influenced by relevant social groups or organizations. Consequently, the social identity (ingroup or outgroup) may have a critical influence on people’s attitudes and behaviors ( Tajfel and Turner, 1986 ; Ali et al, 2020 ). Researchers offer empirical evidence of the vital role of CSR initiatives in affecting individuals’ outcomes.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%